Same same but different: why we should care about the distinction between professionalism and ethics. Issue 1 (December 2016) - Salloch, Sabine
Abstract Medical professionalism forms a belief system which is used to defend physicians' ethos against counterforces which might threaten the integrity of medical practice. The current debates on professionalism, however, are characterized by the lack of a clear distinction between professional and ethical aspects of physicians' conduct. This article argues that a differentiation between professionalism and ethics is not of mere academic interest. Instead, it is of great practical importance with regard to morally contentious issues in medicine. A short analysis of the discussions in history and social sciences reveals that professionalism is more than a catchphrase of modern medical debates but has a complex theoretical background which is still not conclusively understood. Whereas professionalism is clearly linked to the honorable aims of providing services to the individual and the society, it potentially entails problematic aspects, such as elitism, monopoly or the maintaining of power and privileges. With regard to morally contentious topics, the professional ethos of physicians must be differentiated from the perspective of ethics which can take a universal standpoint and has the potential to critically assess context-specific moral norms. The example of the current regulation on suicide assistance in German professional law is taken as an example to demonstrate how professional bodies tend to overstep the limits of their expertise and regulatory power with regard to issues which need an ethical evaluation. The article concludes that the narrowing of ethics and professionalism in public discussions and in medical education should be seen as problematic and that morally contentious topics in modern societies should be open to a participatory and inclusive discussion and democratic decision procedures.